A case-control study to compare the outcome of women treated by two minimally invasive procedures-ultraminilaparotomy myomectomy and laparoscopic myomectomy - Kuo-Chang Wen; Pi-Lin Sung; Wen-Hsun Chang; Huann-Cheng Horng; Yi-Jen Chen; Wen-Ling Lee; Peng-Hui Wang (Elsevier, 2018)
Objective: Ultraminilaparotomy myomectomy (UMLT-M with less 4 cm transverse skin incision) and conventional 3-port wound laparoscopic myomectomy (LM) approaches were proposed as alternative minimally invasive procedures in the management of women with symptomatic uterine myomas but few studies have compared the outcomes of both procedures. Materials and methods: Between January 2002 and December 2003, 71 patients undergoing UMLT-M were compared with those 71 women undergoing LM. The last data collection for all patients was done on 31 December 2016. The parameters for comparison included the characteristics of the uterine myomas, surgical parameters, morbidities, and outcomes. Surgical parameters included the operative time (minutes), estimated blood loss (milliliters), time for removal of drainage, percentage of blood transfusion and co-morbidities. Results: Mean operative time in the LM group was significantly longer than that in the UMLT-M group (208.7 ± 65.9 vs. 98.0 ± 28.2 min, p < 0.001). Intra-operative blood loss was significantly higher in the LM group than that in the UMLT-M group (210.9 ± 184.5 vs. 111.7 ± 108.4 ml, p < 0.001). However, more patients had postoperative fever in the UMLT-M group (39.4% vs. 8.5%, p < 0.001). The recurrence rate of myoma at 5-year follow-up was significantly different between two groups (35.2% of UMLT-M vs. 57.7% of LM, p = 0.007), but there was no difference when follow-up time was over ten years. The location of the myoma recurrence was different between two groups with higher recurrence rates in the fundal and lateral sides of uterus in the UMLT-M group and in the anterior wall of uterus in the LM group. However, the overall symptom control, the need of repeated myoma-related surgery and subsequent pregnancy outcome of both groups seemed to be similar in both groups. Conclusions: More operative time and more blood loss reflected that LM demanded skills, experience and equipment. Therefore, UMLT-M might be a feasible alternative choice in the management of uterine myomas, since it is an easy-to-perform and familiar technique, especially in the absence of suitable equipment or skilled operator. A large and randomized study is needed to confirm the above findings. Keywords: Laparoscopic, Myoma, Myomectomy, Ultraminilaparotomy, Uterus